2015
DOI: 10.1128/jvi.00754-15
|View full text |Cite
|
Sign up to set email alerts
|

The V1V2 Region of HIV-1 gp120 Forms a Five-Stranded Beta Barrel

Abstract: The region consisting of the first and second variable regions (V1V2) of gp120 plays vital roles in the functioning of the HIV-1 envelope (Env). V1V2, which harbors multiple glycans and is highly sequence diverse, is located at the Env apex and stabilizes the trimeric gp120 spike on the virion surface. It shields V3 and the coreceptor binding sites in the prefusion state and exposes them upon CD4 binding. Data from the RV144 human HIV-1 vaccine trial suggested that antibody responses targeting the V1V2 region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 46 publications
6
117
0
Order By: Relevance
“…These conserved gp120 elements are not formed/exposed in the unliganded state of Env but become so after binding to CD4 or the CD4-mimetic compounds (70, 73-76, 86, 89, 95). Our results with the 830A monoclonal antibody from HIV-1-infected humans (107,108) and the 902090 monoclonal antibody from an immunized monkey also suggest that some V2 epitopes on gp120 become readily available for antibody binding after Env exposure to BNM-III-170 binding. The V2i antibody 830A recognizes a discontinuous epitope on the surface of a ␤-barrel composed of V2 strands (108).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…These conserved gp120 elements are not formed/exposed in the unliganded state of Env but become so after binding to CD4 or the CD4-mimetic compounds (70, 73-76, 86, 89, 95). Our results with the 830A monoclonal antibody from HIV-1-infected humans (107,108) and the 902090 monoclonal antibody from an immunized monkey also suggest that some V2 epitopes on gp120 become readily available for antibody binding after Env exposure to BNM-III-170 binding. The V2i antibody 830A recognizes a discontinuous epitope on the surface of a ␤-barrel composed of V2 strands (108).…”
Section: Discussionmentioning
confidence: 58%
“…Our results with the 830A monoclonal antibody from HIV-1-infected humans (107,108) and the 902090 monoclonal antibody from an immunized monkey also suggest that some V2 epitopes on gp120 become readily available for antibody binding after Env exposure to BNM-III-170 binding. The V2i antibody 830A recognizes a discontinuous epitope on the surface of a ␤-barrel composed of V2 strands (108). The C strand (residues 171 to 177) of this V2 ␤-barrel is recognized by the 902090 antibody.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Glycoprotein gp120 has been conventionally divided into five variable and five conserved regions (3), and the region of the first and second variable loops (V1V2) is the most diverse region of Env in both sequence and length (4). However, recent data have shown that V1V2 can form, in the structurally constrained scaffolded V1V2 or the stabilized BG505 SOSIP.664 trimer, a unique five-stranded ␤-barrel structure with strands A, B, C, C=, and D (5,6). In the trimer context, the V1V2 domain is located at the apex of the Env trimer, and the three V1V2 regions in the trimer join together at the center to form a top layer of the Env complex (5,(7)(8)(9).…”
mentioning
confidence: 99%
“…V1V2 also harbors a putative integrin-binding site that may also mediate Env binding to host cells (12)(13)(14). One such site, the tripeptide LD(I/V) motif at amino acid positions 179 to 181 (HxB2 numbering) (15), is located at the beginning of the C= strand in the ␤-barrel (6).…”
mentioning
confidence: 99%